Analisis Tingkat Pemahaman Mahasiswa Universitas Muhammadiyah Palopo Terhadap Bisnis Digital Di Era Modern - Putri, Putri (Income : Digital Business Journal, 2025)
This research aims to analyze the level of understanding of Muhammadiyah University Palopo students regarding digital business trends in the modern era. Advances in news & communication technology have changed the dynamics of global business, resulting in digital business becoming one of the main pillars of the economy. This study uses a narrative qualitative approach using in-depth interviews as the data collection method. Respondents consisted of students from various study programs, selected through purposive sampling to explore diverse perspectives regarding digital business. The research results show that the majority of students have a good basic understanding of digital business concepts, including e-commerce & digital marketing. However, limited campus facilities & lack of easy experience are the primary obstacles to applying this knowledge. This study also found the importance of integrating relevant curriculum using digital efforts and personal training to increase student readiness to face challenges in the digital era. This research contributes to the development of educational policies that can prepare students more effectively to enter the digital-based job market.